1997
DOI: 10.1103/physrevlett.79.143
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of an Anisotropic Energy Gap in Single PlaneBi2Sr2xLa

Abstract: We report angle-resolved photoemission spectra both above and below T c in the single-plane cuprate superconductor Bi 2 Sr 22x La x CuO 61d . The superconducting state measurements show a highly anisotropic excitation gap with a maximum magnitude smaller than that of the bilayer compound Bi 2 Sr 2 CaCu 2 O 8 by a factor of 3. For a range of doping, the gap persists well above T c , behavior previously associated with underdoped bilayer cuprates. The anisotropy and magnitude of the normalstate gap are very simi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
39
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 26 publications
10
39
0
1
Order By: Relevance
“…In an early ARPES experiment, 8 an antinodal superconducting gap of 10±2 meV was observed, which shows good agreement with the LTSH result. This agreement confirms that the superconducting gap essentially follows the simple d-wave form because in ARPES the ∆ 0 is measured directly at the antinodes while in LTSH it is derived from the nodal gap slope v ∆ with the assumption ∆ = ∆ 0 cos(2φ).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In an early ARPES experiment, 8 an antinodal superconducting gap of 10±2 meV was observed, which shows good agreement with the LTSH result. This agreement confirms that the superconducting gap essentially follows the simple d-wave form because in ARPES the ∆ 0 is measured directly at the antinodes while in LTSH it is derived from the nodal gap slope v ∆ with the assumption ∆ = ∆ 0 cos(2φ).…”
Section: Discussionsupporting
confidence: 73%
“…Note that although the dwave pairing has been probed for La-Bi2201 by other experimental techniques such as ARPES, [8][9][10][11][12] present LTSH findings confirm that it is a bulk property of the sample.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…In a compound, the optimal cation states for Sr, La and Bi, are Sr 2+ , La 3+ and Bi 3+ , respectively. Therefore, the substitution of triva- 35 and Harris et al 36 found that as the Bi/Sr ratio increases, and one moves toward the bottom of the phase diagram of the solid solution, the number of holes doped into the system decreases, which thus pushes the system towards the hole-underdoped regime. The lower T c , together with the larger residual resistivity of Bi2201 in comparison with BSLCO (the maximum T c is 38 K 18 ) apparently suggests that the disorder due to (Sr,Bi) substitution is stronger in Bi2201 than the disorder due to (Sr,La) substitution 37 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, ∆ o (T ) is largely undiminished in going from T = 0 to T = T c in underdoped samples, and the size and shape of the gap are basically unchanged through the transition. Add to this the contravariance of T c with the low temperature magnitude of the gap as the doping is changed, and it appears the gap and T c are simply independent energies [134,288]. The gap decreases with overdoping, which may be responsible for the depression of T c in that region, so that the transition may be more conventional on the overdoped side.…”
Section: Applicability To the Cupratesmentioning
confidence: 99%